Surgical Anatomy of Facial Nerve in Rabbits - Abdullah Alhayani, Wissam; MA, Maher; Tariq Hammoodi, Omar (International Journal of Psychosocial Rehabilitation, 2020)
Surgical and anatomical exploration of the extracranial distribution of facial nerve branches has great surgical importance to provide a clear model for nerve surgery. The present study was to illustrate the anatomy of the extracranial branches of the facial nerve in rabbits. Eight adult New Zealand rabbits (clinically healthy, weighing from 2.5 to 3 kg, 4 males and 4 females) had been studied in this investigation. The rabbits divided into two equal groups. In group (A), the rabbits were injected fresh after euthanasia, through the common carotid artery and through the jugular vein, with colored latex to investigate and reveal the course of the facial nerve in relation to facial blood vessels, while in group (B), the rabbits were injected with 10% formalin through the common carotid artery and left for 2-3 days soaked with formalin and then dissected to follow up the branches of the facial nerve. The results showed that the facial nerve in rabbits is a good model for experimental surgery for nerves and has little anatomical variance in its branches with man and other species.